Endogenous hormone causes flower and fruit drop of wax apple (Syzygium samarangense cv. Citra) - Etik Wukir Tini; T.A. Dwi Haryanto; Sakhidin Sakhidin; Saparso Saparso (Advances in Horticultural Science, 2021)
The aim of this study was to obtain information about the content of endogenous hormones that causes ﬂowers and fruit drop of wax apple. The variables observed in the six stages of ﬂower and fruit development that drop easily and retention of indole-3-acetic acid (IAA), cytokinin (zeatin and kinetin), gibberellins (GA3), 1-amino cyclopropane-1-carboxylic acid (ACC), total sugar, and starch. Six stages of development of wax apple fruit: (1) Bud Development (initial ﬂowering) 0-3 days before anthesis. (2) Anthesis (perfect blooming ﬂowers), 0-7 days after anthesis. (3) Fruit set, 7-14 days after anthesis. (4) Fruit development, 14-28 days after anthesis. (5) Fruit Maturation, 28-35 days after anthesis. (6) Fruit ripening, 35-50 days after anthesis. The results showed that the content of IAA, zeatin, GA3, and total sugar of ﬂowers and fruit of wax apple at 6 stages that would fall smaller than those of retention and ACC content and starch was higher in ﬂower and fruits that drop easily than retention. The kinetin content in the ﬂower development that drop easily is smaller than the retention but in the fruit development the kinetin content is not signiﬁcantly diﬀerent between those that drop easily and retention.